EDITOR'S CHOICE: Competition on the range: science vs. perception in a bison–cattle conflict in the western USA. Issue 2 (26th January 2015) - Ranglack, Dustin H.; Durham, Susan; du Toit, Johan T.; Hayward, Matt
Summary Competition between livestock and wild ungulates is commonly perceived to occur on shared rangelands. In the Henry Mountains (HM) of Utah, a free‐ranging population of bison Bison bison has raised concerns among ranchers holding grazing permits on these public lands. Bison are the most conspicuous potential competitors with cattle, but lagomorphs (mainly jackrabbits Lepus californicus) are also abundant in this area. The local ranching community is applying political pressure on state and federal agencies to resolve 'the bison problem', but the relative grazing impacts of bison, cattle and lagomorphs have not previously been quantified. We constructed 40 grazing exclosures (each 5·95 m2) in the conflict area: 20 excluded bison + cattle ('partial') and 20 excluded bison + cattle + lagomorphs ('full'). All exclosures, each with a paired open reference plot, were monitored for 1 year, and above‐ground plant production was measured. GPS telemetry (bison) and scheduled grazing (cattle) allowed visitation to be quantified for each ungulate species based on the number of 'animal days' in the area. Rancher perceptions of wildlife–cattle interactions were recorded in a questionnaire survey. Ranchers perceived bison as a high‐level competitor with cattle, whereas lagomorphs were perceived as low‐level competitors. Grazed reference plots yielded an average (±SE) of 22·7 g m−2 (±5·16) of grass, compared to 36·5 g m−2 (±7·33) in the partial exclosures and 43·7 g m−2 (±7·61) in the full exclosures. Exclusion of large herbivores thus resulted in a 13·8 g m−2 increase in grass biomass relative to the reference plots (P = 0·005), with the additional exclusion of lagomorphs resulting in a further 7·18 g m−2 increase (P = 0·048). Overall, lagomorphs accounted for 34·1%, bison 13·7% and cattle 52·3% of the total grass biomass removed by all herbivores on the shared range. Synthesis and applications. Cattle face a greater competitive challenge from lagomorphs than from bison in the study area. This case study illustrates the need for science‐based management of social–ecological systems in which even long‐term resource users might underestimate the complexities of trophic interactions. Attention should be redirected at the lagomorphs and their main predators, coyotes Canis latrans, which are currently subject to population control. To reduce negative perceptions among local ranchers, options should be explored to incorporate benefit‐sharing into the management of the bison population.